Clear Cell Morphology in a Salivary Gland Tumor - Clearly a Morphological Dilemma - Marla, Nisha J; T, Poorni Bharathi (Annals of Pathology and Laboratory Medicine, 2020)
Primary salivary gland tumors with clear cell morphology comprise an uncommonly encountered subgroup of salivary gland neoplasm. Clear cell morphology is a known feature in both benign and malignant salivary gland tumors. Oncocytomas are uncommon tumors of the salivary gland. They have an abundance of mitochondria, which is manifested as granular eosinophilic cytoplasm by light microscopy with presence of cytoplasmic glycogen. Fixation artifact can impart cytoplasmic clearing and oncocytomas with a predominance of clear cytoplasm are labeled Clear cell oncocytomas. Accurate diagnosis of salivary gland tumors can be challenging because of the many diagnostic entities, extensive morphologic overlap, and the rarity of most tumor types. Here we report a case of Clear cell salivary oncoctyoma which was confirmed by Immunohistochemical markers by excluding morphological differential of Clear cell myoepithelioma.